Savannah fires and local resistance to transnational land deals: The Case of Organic Mango Farming in Dipale, Northern Ghana - Yaro, J.A; Tsikata, D (Routeledge, 2013)
Recent interest in investments in land in Africa targets the supposed ‘abundant and wasting’ fire-prone savannah woodlands. Outgrower models are becoming the recommended business model for transnational investments as they are argued to guarantee a win–win outcome for both trans-national companies and local farmers. Using qualitative interviews in the village of Dipale, we investigate one such project, the Integrated Tamale Fruit Company (ITFC). All outgrowers lost their investments to savannah fires and consequently abandoned or converted the mango farms into food crop farms. The political ecology of the area, manifested in the human-environmental conditions and land management practices confounded the business model of land acquisitions thus threatening their profitability for the investors and reducing their contribution to local livelihood outcomes. The savannah fires represent an instrumentalized form of local resistance against the expropriation of their livelihood resources without their full cooperation and consent.
Keywords: Savannah fires; outgrowers; land deals; Savannah woodlands; Northern Ghana